Family, capitalist modernization and democracy: returning to some milestones of the longstanding debate on the transformations of the family in Brazil (Tempo e Argumento, 2011)
The article analyzes the transformation of the family in Brazil under the influence of capitalist modernization and libertarian social movements in defence of democracy, of freedom and equality, of the recognition of differences, and of human and individual rights. In a non-exhaustive manner it aims to touch on some of the major milestones in these changes, with special emphasis on the post-1964 period. In this period, modernizing processes accelerated and a revolution in values took place, leading to the crisis of the family of the 1970s and its passage over the following decades, from the traditional authoritarian and hierarchical model to other more democratic and egalitarian forms of organization.
Keywords: family; capitalist modernization; modernization; democracy; feminism